Analisis Realita Pandemi Indonesia Dalam Film Hari Yang Dijanjikan - Nuril Anggraini; Sumaina Duku; Jawasi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Film, as a means of mass communication, has an important role in conveying messages to a wide audience in the current digital era. Not just a form of entertainment, films are also artistic and cultural expressions that reflect social and cultural realities and have a significant impact on viewers through the messages they convey. The research entitled Analysis of the Reality of the Indonesian Pandemic in the Film The Promised Day aims to analyze how the film The Promised Day by Fajar Bustomi depicts the reality of the COVID-19 pandemic in Indonesia. The research approach used is a qualitative approach with a type of descriptive research that focuses on analyzing the meaning contained in the film. Analysis was carried out on film scenes using Roland Barthes' semiotic analysis technique, paying attention to the meaning of denotation, connotation and myth implied in each scene. The data collection technique begins with making observations. In the context of the research, the initial stage involved selecting texts and images related to the film "The Promised Day" with a holistic observation approach to the overall narrative and visual elements presented in the film. This procedure was continued with the data collection process related to the film The Promised Day. The collected data was then analyzed by researchers. After the collected data is classified, analysis is carried out by applying Roland Barthes' Semiotic analysis techniques which include denotation, connotation and myth as the main analysis tools. Through this semiotic theory approach, a film is not only interpreted at the level of an explicitly revealed narrative, but also explored to identify the myths implicit in the narrative. This film shows a story that is very relevant to the current condition of Indonesian society, especially in facing the impact of COVID-19 pandemic. Through various scenes in the film, various aspects of the impact of the pandemic, such as economic, health, educational and social, are depicted in detail. The research results show that the film The Promised Day succeeded in strongly reflecting the reality of the pandemic in Indonesia, through its depiction of the situation and struggles faced by Indonesian people in facing the COVID-19 outbreak. The conclusions of this research provide a deeper understanding of the reality of the pandemic in Indonesia through the medium of film, and have the potential to contribute to the development of science and knowledge in the fields of film analysis and communication studies.